Complex, Intelligent, and Software Intensive Systems Proceedings of the 11th International Conference on Complex, Intelligent, and Software Intensive Systems (CISIS-2017) (Advances in Intelligent Systems and Computing,, 2018)
This book gathers the proceedings of the 11th International Conference on Complex, Intelligent, and Software Intensive Systems (CISIS-2017), held on June 28-June 30, 2017 in Torino, Italy. Software Intensive Systems are characterized by their intensive interaction with other systems, sensors, actuators, devices, and users. Further, they are now being used in more and more domains, e.g. the automotive sector, telecommunication systems, embedded systems in general, industrial automation systems and business applications. Moreover, the outcome of web services delivers a new platform for enabling software intensive systems. Complex Systems research is focused on the understanding of a system as a whole rather than its components. Complex Systems are very much shaped by the changing environments in which they operate, and by their multiple internal and external interactions. They evolve and adapt through internal and external dynamic interactions. The development of Intelligent Systems and agents, which invariably involves the use of ontologies and their logical foundations, offers a fruitful impulse for both Software Intensive Systems and Complex Systems. Recent research in the fields of intelligent systems, robotics, neuroscience, artificial intelligence, and cognitive sciences is essential to the future development of and innovations in software intensive and complex systems. The aim of the volume "Complex, Intelligent and Software Intensive Systems" is to provide a platform of scientific interaction between the three interwoven and challenging areas of research and development of future Information and Communications Technology (ICT)-enabled applications: Software Intensive Systems, Complex systems and Intelligent Systems.